DECISION SUPPORT SYSTEM DETERMINATION OF CUSTOMER SATISFACTION LEVEL OF ORIFLAME PRODUCTS WITH ANALYTIC HIERARCHY PROCESS METHOD - Muhamad Muslihudin; Nur Latifah; Trisnawati Trisnawati (Bakti Nusantara Institute, 2021)
In order to improve customer satisfaction with Oriflame products, customer satisfaction was studied. Find out how Oriflame can satisfy customers through its products, services, finances, delivery, and company conditions. In this research, information marketing research is needed to understand how customers behave and the criteria that are very important when deciding how customers make decisions about Oriflame products. At this stage of research, researchers analyze existing systems by conducting library research and direct observation. In order to calculate the customer satisfaction level, the AHP (Analytic Hierarchy Process) method is used. By using this decision support system, it is expected to make it easier for companies and sellers to determine customer satisfaction with Oriflame products.